Utopia and Reality : El Lissitzky, Ilya and Emilia Kabakov. - The State Hermitage Museum, St. Petersburg; Multimedia Art Museum, Moscow; Groys, Boris; Kabakov, Ilya; Kabakov, Emilia; Ozerkov, Dimitri; Sviblova, Olga (St. Petersburg : The State Hermitage Museum, 2013)
El Lissitzky ; Kabakov, Ilya ; Kabakov, Emilia
The State Hermitage Museum, St. Petersburg, June 28 - August 25, 2013 / Multimedia Art Museum, Moscow, September 17 - November 24, 2013
kunstcatalogus